The short-short story: a new literary genre - Jose Flavio Nogueira Guimaraes (2010)
This thesis proposes a study of a new postmodern prose fiction genre, the short-short story. Considerations of generic classifications and boundaries are followed by an historical overview and analysis of short fiction from the nineteenth to twenty-first centuries, especially under the influence of the Russian Anton Chekhov, who is regarded as the father of the modern short story. The postmodern short-short story is seen as emerging from this trend, a hybrid genre with characteristics of the narrative language of other prose genres such as the short story and the journalistic writing. The cluster of features, such as condensation, lack of character development, surprise endings, etc., which is seen as characteristic of the short-short story are discussed, and ten examples are summarized and analyzed, including two traditional short stories for contrast. It is seen that the short-short story may be further broken into what is called 'the new sudden fiction', and the even shorter and more radical 'flash fiction'.